Motetten am Hof Maximilians II. (1527-1576) Komponieren im Zeitalter der Konfessionalisierung - Pfohl, Jonas (2022)
In the present volume sacred motets composed by members of the chapel of the Archduke and later Emperor Maximilian II - among them Jacobus Vaet, Philippe de Monte and Jacob Regnart - are documented and analysed for the first time. The chapel and its repertoire cultivated at the court not only served as a means for the representation of the court but also needed to comply with the emperor's personal artistic and religious wishes. Maximilian II officially confessed to the Roman-Catholic church but personally sympathised with the Reformation. Therefore, the analysis of the texts and music addresses also the question of how the gap between the Roman-Catholic ceremony at court and the emperor's personal faith is reflected in motets.